Biblioterapijos, skaitymo ir gyvenimo kokybės sąsajos: tarpdisciplininis požiūris - Janavičienė, Daiva (Knygotyra, 2005)
Culture is revealed through communication. Culture in a knowledge society cannot be separated from the public and free word in books. The public word in books and mass media is important in many respects. Recently, we could only read popular information on psychology in secret printing presses, with copies traveling from hand to hand. Any restrictions encroach on human quality of life. The action of forbidding something (such as using a national language) is an evident dishonor to a nation's quality of life.The purpose of this article is to analyze the concepts of: 1) quality of life, 2) reading, and 3) bibliotherapy connections.Every concept used in the title of the report has more than one meaning. The quality of life is a broad and often-used concept. To increase quality means to do something in a better way, or the opposite. In the article, concrete indicators are supported with the expressed and measured term "quality of life," which is connected with a country’s citizens' welfare and social development. There are three main indicators of social development: literacy rate, life expectancy, and capital stock. According to these, the enumerated index is also called the quality of life by some scientists (Baris K. Yoruk, Osman Zaim). The ideas of this article are supported according to this point of view.All three indicators that describe a society's quality of life can be associated with reading. There is a possible presumption that reading skills and their successful usage depend on educational achievements—literacy rate (the first indicator of the quality of life). The quality of life is also expressed through the influence of the other two indicators, which are:• How much time a person realistically has and will have for reading (life expectancy—how long the person is going to live—does not include the person's intention to allocate time or attention to such an activity from their own free time). Does the acquired education encourage a person to remain curious and seek wisdom through reading throughout life?• Within the limits of the second indicator (the level of capital stock) of quality of life, the question is formulated: how many financial resources can a person allocate for desired activities (referring to whether a person's level of capital stock allows them to satisfy their reading requirements—limiting the possibility to buy desired books and documents). Will the acquired education encourage the person to attribute books and other documents to the necessary resources for achieving a normal level of life?Conclusion: In this work, the concepts of quality of life, reading, and bibliotherapy are analyzed. Their interconnected interaction can be defined as: Bibliotherapy, supported by reading technologies and dialogues, can be used as a method to improve a person's quality of life.